Estudos etnopedológicos em neossolos sob diferentes usos agrícolas no assentamento Santa Agostinha, RN - Silva, Jucirema Ferreira da (2015)
In Brazil, investigations performed for the purpose of classification and characterization of soil attributes that take into account the knowledge of the local community are still scarce, perhaps this condition is explained by the challenges of ethnopedological approach that anthropological factors dialogue like this way of understanding spaces of production and reproduction of life. In this context, this study aimed to characterize and classify agricultural soils through morphological, physical and chemical analyzes using the Ethnopedological studies and infer about the methods and their importance to the agricultural production of the Settlement Project Santa Agostinha, Caraúbas, RN. The five units defined for the study were: 1) cashew; 2) capineira; 3) consortium; 4) and agroforestry; 5) preserved forest (reference). Participatory workshops were held, emicista exchanges and classification and ethicist and analysis of morphological attributes, physical and chemical soil in the units studied in layers 0.0-0.10; 0.10-0.20; 0.20-0.30 m their diagnostic profiles. The samples were sent to the Federal Rural University of the Semi-Arid for processing thin dry land to air (TFSA) and subsequent analysis of the physical and chemical properties. Was used to interpret the results multivariate statistics. The results of the ethicist rating based on the interpretation of the analyzed attributes were as follows, according to the units: Neosol Quartzarenic and Neosol Regolitic showed a close relationship with emicista rating. The consortium agricultural unit had physical limitations, when the drainage, waterproof layer, which favors the accumulation of water in subsurface stimulating agricultural production in other units as the chemical solódico character, masked fertility. The experiences of the peasants in participatory workshops and exchanges provided exchange of popular and scientific knowledge, as well as new prospects for coexistence with the semiarid region